PELAKSANAAN PERJANJIAN KERJASAMA DALAM PENGELOLAAN HOTEL ANTARA SOFYAN HOTEL DENGAN SAKA HOTEL - AGUNG NUGRAHA (PREMISE LAW JURNAL, 2016)
This is the underlying idea of of the research on the coorperation agreement in management between Sofyan Hotel and Saka Hotel with the problems as follows: how about the rights and responsibilities of all parties involved in the cooperaton agreement in management between Sofyan Hotel and Saka Hotel, and how about the settlemment of the legal dispute in the cooperation  agreement in management between Sofyan Hotel and Saka Hotel. The research applied the descriptive method with judicial empirical approach. This results showed that in the implementation of the cooperation agreement in the management of Sofyan Hotel and Saka Hotel Medan between Sofyan Hotel and Saka Hotel was made in underhanded contract and in standard form. In this case, one of the parties was weak and not in the position to bargaining. As to cooperation agreement, Sofyan Hotel is more profitable it is the one that makes the contract which is for its own sake. Meanwhile, when one of the parties defaults, a negotiation will be made for a good solution. However, in case a negotiation is not effective, a legal remedy is made by bringing the dispute to the central Basyarnas (National Sharia Arbitration Agency). Keywords: Cooperation Agreement, Hotel Management